Heat transfer in multi-phase materials - Ochsner, Andreas; Murch, Graeme E. (Advanced Structured Materials, 2011)
This book provides a profound understanding, which physical processes and mechanisms cause the heat transfer in composite and cellular materials. It shows models for all important classes of composite materials and introduces into the latest advances. In three parts, the book covers composite materials (Part I), porous and cellular materials (Part II) and the appearance of a conjoint solid phase and fluid aggregate (Part III).